An Adaptive fuzzy-PD inertial control strategy for a DFIG wind turbine for frequency support - Thelfa Ahmad; Tim Littler; Wasif Naeem (AMTS and Faculty of Engineering - Universitas Riau, 2020)
With increasing levels of wind generation in power systems, guaranteeing continuous power and system’s safety is essential. Frequency control is critical which requires a supplementary inertial control strategy. Since wind power generation depends directly on wind conditions, this creates an immense challenge for a conventional inertial controller with parameters suitable for all power grid operations and wind speed conditions. Therefore, tuning the controller gains is absolutely critical for an integrated conventional/renewable power system. Here, a fuzzy-logic adaptive inertial controller scheme for online tuning of the proportional-derivative-type (PD) inertial controller parameters is proposed. The proposed controller adapts the control parameters of the supplementary inertial control of the doubly fed induction generator (DFIG) wind turbine so that with any disturbance such as load changes, the active power output can be controlled to mitigate the frequency deviation. Simulation results indicate that the proposed adaptive controller demonstrates a more consistent and robust response to load changes compared to a conventional controller with fixed parameters.